KEMAMPUAN PEMBIAYAAN DAN EFISIENSI OPERASI SERTA URGENCY GOOD CORPORATE GOVERNANCE DALAM PENCAPAIAN LABA PADA BPR SYARIAH DI JAWA TIMUR - Hanif, Rifki; Fitri, Raisa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Syariah Banking is increasingly recognized by the government as shown by the increasing number of banks conducting business based on sharia principles in 2011. In 2011, banking performance showed a positive development supported by high profitability, and other financial indicators that showed positive growth. This study aims to determine the effect of Operating Costs and Income, Loan Asset Ratio, and Good Corporate Governance to Achievement of Profit in Islamic Rural Banks in East Java. This study uses multiple regression analysis model. And the type of data is secondary data taken from Bank Indonesia Report. The findings show BOPO has no partial effect on Profit. BOPO, LAR and GCG influence simultaneously to earnings. The implication of this research is that BPRS must be able to reduce operational cost and able to increase credit and apply GCG so that it will affect the achievement of profit at the BPRS in East Java.